The influence of Au‐nanoparticles presence in PDMS on microstructures creation by ion beam lithography. (3rd June 2020) - Romanenko, Oleksandr; Slepička, Petr; Malinsky, Petr; Cutroneo, Mariapompea; Havránek, Vladimír; Stammers, James; Švorčík, Václav; Macková, Anna
Abstract : 3D microstructures in pure poly(dimethylsiloxane) (PDMS) and PDMS with embedded Au nanoparticles were prepared by ion beam lithography without any further etching. Two mega‐electron volts helium and 10 MeV oxygen ions were used for ion microstructuring. Parallel lines of 1 mm in length and 10 μm in thickness were fabricated for investigation of the effect of the nanoparticles presence in the polymer on the surface morphology of the created microstructures. The created microstructures were checked by optical microscope. Infrared (IR) spectrometry was used to study the effect of the ions type and fluence on the chemical changes of the material. Atomic force microscopy was used for the fine detail study as well as for checking the microstructure quality. Analysis revealed an increased radiation resistance of the nanocomposite compared to the pure PDMS. Shrinkage is proportional to the fluence, but the maximum value for both materials is limited by saturation. 3D microstructure in modified PDMS obtained at the same irradiation condition as pure PDMS is characterized by its smaller height. Obtaining the microstructure in nanocomposite of the same height as in pure PDMS by increasing the fluence can be impossible due to saturation of shrinkage and/or radiation‐induced heating of the material.